2011
DOI: 10.1177/1470357210389538
|View full text |Cite
|
Sign up to set email alerts
|

When words fail us: using visual composites in research reporting

Abstract: This article describes a use of visual imagery in research reporting that helps to emphasize the human and social dimensions of research issues and encourage different ways of thinking about the findings and implications. During the literature review, in order to establish the authors’ longitudinal research into adult literacy, they observed that research participants’ own perspectives and rich life-worlds were usually invisible in final reports and articles, submerged under layers of governmental or scholarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The literature recommends the use of multiple modalities when communicating higher‐level concepts. In an analysis of research reporting, Sligo and Tilley (2011) found the use of visual imagery more effective than words alone. Likewise, among a group of 13–14‐year‐olds, Reiss, Boulter, and Tunnicliffe (2007) found the expression of concepts through drawing tied to higher‐level thinking among the children.…”
Section: Prognosis For the Futurementioning
confidence: 99%
“…The literature recommends the use of multiple modalities when communicating higher‐level concepts. In an analysis of research reporting, Sligo and Tilley (2011) found the use of visual imagery more effective than words alone. Likewise, among a group of 13–14‐year‐olds, Reiss, Boulter, and Tunnicliffe (2007) found the expression of concepts through drawing tied to higher‐level thinking among the children.…”
Section: Prognosis For the Futurementioning
confidence: 99%
“…The literature recommends the use of multiple modalities when communicating higher‐level concepts. In an analysis of research reporting, Sligo and Tilley (2011) found the use of visual imagery more effective than words alone. Likewise, among a group of 13–14‐year‐olds, Reiss, Boulter, and Tunnicliffe (2007) found the expression of concepts through drawing tied to higher‐level thinking among the children.…”
Section: Prognosis For the Futurementioning
confidence: 99%
“…In relation to the latter, which is our area of interest, two recent studies provide excellent examples. Bartlett (2013), in her examination of the social activism of people with dementia, made use of cartoons to represent and present findings, while Sligo and Tilley (2011) used visual composites to present data from participants about their experiences of literacy and an adult literacy program. There were limitations noted with both of these visual approaches, respectively: for example, people often have strong reactions to cartoons, or question the role of humour in talking about a sensitive or difficult issue; and visual methods may not be seen as sufficiently formal or rigorous for funders or policy makers; or pictures may be interpreted in many ways.…”
Section: Creative Strategies For Sharing and Encouraging Knowledge Usementioning
confidence: 99%
“…Of interest to us here is that, both from Bartlett (2013) and Sligo and Tilley’s (2011) research, participants could be seen to belong to marginalized groups. One other hidden group in our community are children whose parent/s are in prison – our focus in this project.…”
Section: Creative Strategies For Sharing and Encouraging Knowledge Usementioning
confidence: 99%